Penicillium simplicissimum NL-Z1 Induced an Imposed Effect to Promote the Leguminous Plant Growth - Zhuang, Jiayao; Liu, Chao; Wang, Xiaoxue; Xu, Tongxin; Yang, Hao (Frontiers in Microbiology, 2021)
It is found effective for phytoremediation of the guest soil spraying method by adding microbe to promote the growth of arbor leguminous plant on the high and steep rock slope. However, its underlying mechanisms remain elusive. Here, some experiments were conducted to explore the multi-functions of P. simplicissimum NL-Z1 on the rock weathering, nodule growth, and beneficial microbial regulation. The results show that P. simplicissimum NL-Z1 significantly increased the release of phosphorus, potassium, calcium, and magnesium from the rock by 226%, 29%, 24% and 95%, respectively, as compared with the control. A significant increase of 153% in the Indigofera pseudotinctoria Matsum nodules biomass, accompanied by an increase of 37% in the leguminous plant biomass was observed in the P. simplicissimum NL-Z1 treatment than the control treatment. Interestingly, even though P. simplicissimum NL-Z1 itself became a minor microbial community in the soil, it induced a significant increase of Mortierella who as a beneficial microbe can promote phosphate-solubilizing and plant growth. The results suggest that P. simplicissimum NL-Z1 could induce an imposed effect to promote the leguminous plant growth, which may be conducive to the development of phytoremediation technique for the high and steep rock slope. The study provides a novel thought of using the indirect effect of microbes, i.e., promoting other beneficial microbes, to improve soil environment.